Women’s experiences of maternity care in England: preliminary development of a standard measure - Redshaw, M; Martin, C; Savage-McGlynn, E; Harrison, S (BioMed Central, 2019)
BACKGROUND:As maternity services evolve and the population of women served also changes, there is a continuing need to effectively document the views of women with recent experience of care. A woman's maternity experience can have a positive or negative effect upon her emotional well-being and health, in the immediate and the long-term, which can also impact the infant and the wider family system. Measuring women's perceptions of maternity services is an important way of monitoring the quality of care provision, as well as providing key indicators to organisations of the services that they are providing. It follows that, without information identifying possible areas in need of improvement, it is not clear what changes should be made to improve the experiences of women during their journey through maternity services from pregnancy to the early weeks at home with a new baby . The objective is to describe the development process and psychometric properties of a measure of women's experience of maternity care covering the three distinctly different phases of maternity - pregnancy, labour and birth, and the early postnatal period. METHODS:Data from a national survey of women who had recently given birth (n = 504) were used. Exploratory and confirmatory factor analytic methods were employed. The measure was assessed for underlying latent factor structure, as well as for reliability, internal consistency, and validity (predictive, convergent and discriminant). RESULTS:The models developed confirmed the use of three separate, but related scales about experience of maternity care during pregnancy, labour and birth and the postnatal period. Data reduction was effective, resulting in a measure with 36 items (12 per scale). CONCLUSION:The need for a psychometrically robust and qualitatively comprehensive measure of women's experience of maternity care has been addressed in the development and validation of this prototype measure. The whole measure can be used at one time point, or the three separate subscales used as individual measures of experience during particular phases of the maternity journey with identified factor structures in their own right.